Tarannum Smart Learning Application: Embracing the beauty of tarranum through multimedia technology - Hapini Awang; Mohd Zaini Zakaria; Abdulrazak F. Shahatha Al-Mashhadani; Ramlan Mustapha; Mohd Faiz Mohd Yaakob; Adnan Mohamed Yusof; Nusairah Ramli; Mohd Nur Adzam Rasdi; Mohd Fairuz Jafar; Farah Muhamad Zain; Marini Kasim; Aliff Nawi (Institute of Advanced Engineering and Science, 2022)
This article discusses the development procedures of the Tarannum Smart Learning Application (Tarannum-SLA). It is a teaching and learning aid that has been developed for those who are interested in the tarannum subject. The tarannum is a technique to beautify and curve the tone of voice, in a certain tempo and rhythm when reading the Quran. The main aim of Tarannum-SLA is to facilitate the process of learning tarannum. Also, this courseware could create awareness among Muslims on the importance of the Quran. The Tarannum-SLA was developed not only to attract Muslims but also for non-Muslims who are interested to know about Islam, especially in terms of the arts of Quran recitation. Furthermore, in this courseware, we provide three language options, which are Malay, English, and Arabic for the convenience of our diverse prospective users. There are seven styles of tarannum, including Bayyati, Nahwand, Hijaz, Rast, Soba, Jiharkah, and Sika that are included in the Tarannum-SLA. Furthermore, to examine the ability of Tarannum-SLA to tackle the users’ needs, we have conducted the usability analysis based on the diffusion of innovation model. The result indicated that most of the constructs are perceived at a high level by respondents. Thus, this evidenced the high usability of Tarannum-SLA in promoting Quranic education. Although the development of this courseware has reached the implementation stage, it still needs some future improvements, for example, to amend the verses and reciters.